DECISION SUPPORT SYSTEM FOR THE DETERMINATION OF WEB-BASED GAYO ARABICA COFFEE BEANS WITH WEIGHTED PRODUCT (WP) METHOD - Nurul Hamdi (Sean Institute, 2021)
The weakness of coffee entrepreneurs during this time is still the lack of knowledge about the sorting of the assessment the results sorting of coffee beans. So far the selection of coffee beans is still using the manual way but the coffee beans will be in the process will be sorted election to determine the quality. This condition causes producers inefficient and accurate in determining the quality of coffee beans because of insufficient technology to manage the quality determination of coffee beans that require manufacturers to analyze the quality of coffee beans using a system based on standardization assessment by the International coffee organization (ICO). To facilitate the manufacturer in this case, the authors build a decision support system of the determination of the sorting of coffee beans that can provide solutions that have been faced to produce quality coffee beans. To support this research, the data collection criteria from the International coffee organization (ICO) as data to conduct the quality assessment. The decision support system is formed using PHP, HTML, and MYSQL programming language as system database, weighted product as its design method. this decision support system is built by adding criteria to reduce the level of subjectivity, and the impact on the results of determining the quality of coffee beans is given to be more accurate and precise.